Peningkatan Keterampilan Menulis Teks Eksplanasi Menggunakan Model Kooperatif Think Talk Write Peserta Didik Kelas V SDN 23 Balai Naras Kota Pariaman - Putri Adrian; Muhammadi Muhammadi (Pusat Riset dan Inovasi Nasional, 2025)
This research is motivated by the reality in the field that shows the low skills of writing explanatory texts of students in grade V of SDN 23 Balai Naras, Pariaman City. This is because teachers do not develop learning models and media and teachers still have not implemented three things that are the basis for learning to write, namely pre-writing activities, during writing, and post-writing so that students are less interested in learning to write. This study aims to describe the improvement of explanatory text writing skills using the Think Talk Write cooperative model in grade V students of SDN 23 Balai Naras, Pariaman City. This type of research is Classroom Action Research (CAR) using qualitative and quantitative approaches. This research was conducted in two cycles, each cycle has stages of planning, implementation, observation, and reflection. The subjects in this study were teachers and grade V students totaling 25 people consisting of 14 males and 12 females. The results of the study showed an increase, in the teaching module in cycle I obtained an average value of 89.06% Good (B), then increased in cycle II with an average value of 96.87% very good (SB). The assessment of the teacher aspect in cycle I obtained an average value of 85% Good (B), increasing in cycle II with an average value of 95% very good (SB). The assessment of the student aspect in cycle I obtained an average value of 85% Good (B), increasing in cycle II with an average value of 95% very good (SB). The assessment of the knowledge aspect in cycle I obtained an average value of 68.8% less (D) increasing in cycle II with an average value of 83.2% good (B). The assessment of the skills aspect in cycle I obtained an average value of 70.73% sufficient (C) increasing in cycle II with an average value of 87.31% good (B). It can be concluded that the cooperative think talk write model can improve the writing skills of explanatory texts of students in class V of SDN 23 Balai Naras, Pariaman City.